NANODIMENSIONAL AND SUPERDISPERSED PARTICLES IN FOUNDRY TECHNOLOGIES - O. S. Komarov; V. I. Volosatikov; I. B. Provorova; T. D. Komarova; K. E. Baranovsky (Литьë и металлургия, 2014)
Analysis of existence of initial raw materials for production of the superdispersed powders Al(OH)3  and Al2O3 in the Republic of Belarus is given, and also parameters of technological process of their production by sol-gel method are determined. Data on degree of efficiency of additions of powders to the traditional modifiers eliminating chill in castings of gray cast iron is provided.